PENGARUH MEDIA TANAM DAN DOSIS PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAHE EMPRIT (Zingiber officinale var. amarum): jahe emprit, kandang, media, pupuk, tanam - KOBAN, ROSITA LUSIA TADA; Ratna Nurhayati, Dewi; Sigit Saputro, Avisema (innofarm, 2024)
Abstract. This study aims to investigate the effect of planting media and the dose of cow manure on the growth and yield of ginger bucket (Zingiber of icinale var. amarun). The use of research materials includes the rhizome of emprit ginger of the local variety Jumantono, dumplings, cow dung, rice husks, cocopeat, decomposer (M21). The equipment used includes polybags measuring 30 cm x 30 cm, hoes, pencils, books, meters, raffia ropes, nameplates, cutters, cameras, 70% paranets. The research was conducted in February 2024 - July 2024 at the Experimental and Research Garden, Faculty of Agriculture, Unisri Mojosongo. This study uses 2 complete factors Random Design (RAL) with 3 replications. The planting medium is soil (M0), soil (M1) + rice husks, (M2) soil + husk charcoal, (M3) soil + cocopeat. The dosage of cow manure is (K0) 0 g/plant, (K1) 150 g/plant, (K2) 200 g/plant, (K3) 250 g/plant. The results of the observation data were analyzed using various annova fingerprints with a 5% level test and some further tests Duncan. Parameters: plant height, number of leaves, leaf color, rhizome weight, rhizome length and number of rhizomes. The only parameters that affect are the height of the plant, the number of leaves, the weight of the rhizome and the length of the rhizome. The planting medium was influenced by the highest husk charcoal yield (M2). The use of cow manure is influential with the highest dose result of 250 g/plant. The interaction of the two with the highest yield (M2K2) of soil and husk charcoal + cow manure dose of 200 g/plant.